SWOT and IFE EFE Analysis in the Development of Geothermal Power Plant in Mount Slamet Area: Ecological and Social Opportunities and Challenges - Ajeng Faizah Nijma Ilma; Wulandari, Maria Mu’ti; Jati, Baginda Khalid Hidayat (LP2M IAIN Palopo, 2025)
The Geothermal Power Plant (PLTP) development in the Slamet Mountain area aims to provide sustainable energy while facing ecological and social challenges. A SWOT analysis reveals strengths like abundant geothermal resources and strong government support, but also weaknesses such as inadequate infrastructure and high costs. Opportunities include rising public awareness of clean energy and eco-tourism, while threats involve environmental damage and social displacement. The Internal Factor Evaluation (IFE) score is 3.05, indicating moderate strengths, and the External Factor Evaluation (EFE) score is 3.00, revealing significant opportunities and threats. To achieve sustainable development, a collaborative approach with stakeholders is recommended, focusing on strengthening infrastructure, establishing clear regulations, and fostering community engagement.